2010
DOI: 10.1007/s11430-010-4017-9
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotopic composition and source identification of atmospheric environment in central Zhejiang, China

Abstract: Sulfur dioxide and sulfate aerosols in the atmosphere are significant factors leading to acidification of the atmospheric environment and worsening the pollution of acid deposition. Because of the "fingerprint" characteristics of the stable sulfur isotopic composition, sulfur isotope has been widely adopted in environmental researches concerning sulfur cycle and source identification. In this study, the atmospheric environment of Jinhua City, central Zhejiang Province, was continuously monitored, and the sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Previously, the negative correlation between δ 34 S-SO 4 2− and SOR was also found in Nanjing, China, during a haze episode, indicating that SO 2 oxidation would change δ 34 S-SO 4 2− values. 43 Zhang et al 44 suggested a high RH enlarged the surfaces of droplets and wet aerosols in the atmosphere, which resulted in the aqueous-phase oxidation reactions of atmospheric SO 2 with oxidants. In addition, the significant correlation between δ 34 S and RH might suggest that isotope fractionation occurred in aqueous-phase oxidation of SO 2 to sulfate formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previously, the negative correlation between δ 34 S-SO 4 2− and SOR was also found in Nanjing, China, during a haze episode, indicating that SO 2 oxidation would change δ 34 S-SO 4 2− values. 43 Zhang et al 44 suggested a high RH enlarged the surfaces of droplets and wet aerosols in the atmosphere, which resulted in the aqueous-phase oxidation reactions of atmospheric SO 2 with oxidants. In addition, the significant correlation between δ 34 S and RH might suggest that isotope fractionation occurred in aqueous-phase oxidation of SO 2 to sulfate formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this study, the range of δ 34 S-SO 4 2− in North China was 0.8-7.5‰, with the tendency corresponding well to the values of source coals (6.6‰) (Maruyama et al, 2000;Yetang et al, 1993). Sulfur isotopic composition varied greatly in southern coal due to regional differences, for example, the δ 34 S coal ranges in the Pearl River Delta, Southeast China, and Southwest China were 3.1-6.7‰ (Liu et al, 1996;Xiao et al, 2015;Zhang et al, 1995;Zhang et al, 2010), −0.7-10.2‰ (Chameides and Stelson, 1992;Zhang et al, 1995;Zhang et al, 2010), and − 1.7-5.4‰ (Yetang et al, 1993;Zhang et al, 2002;Zhang et al, 2010), respectively. The ranges of δ 34 S-SO 4 2− in the Pearl River Delta, Southeast China, and Southwest China was 3.5-4.4‰, 0.2-2.9‰, and 4.8-5.7‰, respectively, which were close to the δ 34 S coal values at the sites.…”
Section: Spatial Distribution Of Sulfate and Their Isotopes And Possi...mentioning
confidence: 99%
“…Some field studies synchronously measured the δ 34 S values in ambient SO 2 and SO 4 2– samples. ,, They found significant differences (>2‰) of δ 34 S values between SO 2 and particulate SO 4 2– in central and northern China, providing evidence to support the fractionation effects of δ 34 S through the transformation of SO 2 into SO 4 2– . The significant fractionation effects were responsible for the apparent seasonality of δ 34 S-SO 4 2– in the atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the fractionation factors of δ 34 S (α 34 S g→p ) through SO 2 oxidation were temperature-dependent, except for that of the SO 2 + NO 2 oxidation pathway. , Compared to SO 2 oxidation by OH, H 2 O 2 /O 3 , and NO 2 , only transition-metal-ion (TMI) catalytic oxidation of SO 2 possessed the negative fractionation factors . Previous many studies have suggested that α 34 S g→p values should be considered in quantification of emission sources to sulfate when the fractionation effects of δ 34 S were significant; otherwise, the estimated source apportionments to sulfate might be more uncertain. ,, In spite of this, none of the previous studies have considered the fractionation effects of δ 34 S when apportioning the emission sources of sulfate by sulfur isotope compositions. , …”
Section: Introductionmentioning
confidence: 99%